Bacteriophage MS2 genomic RNA encodes an assembly instruction manual for its capsid. Issue 1 (2nd January 2016) - Stockley, Peter G.; White, Simon J.; Dykeman, Eric; Manfield, Iain; Rolfsson, Ottar; Patel, Nikesh; Bingham, Richard; Barker, Amy; Wroblewski, Emma; Chandler-Bostock, Rebecca; Weiß, Eva U.; Ranson, Neil A.; et al.
ABSTRACT: Using RNA-coat protein crosslinking we have shown that the principal RNA recognition surface on the interior of infectious MS2 virions overlaps with the known peptides that bind the high affinity translational operator, TR, within the phage genome. The data also reveal the sequences of genomic fragments in contact with the coat protein shell. These show remarkable overlap with previous predictions based on the hypothesis that virion assembly is mediated by multiple sequences-specific contacts at RNA sites termed Packaging Signals (PSs). These PSs are variations on the TR stem-loop sequence and secondary structure. They act co-operatively to regulate the dominant assembly pathway and ensure cognate RNA encapsidation. In MS2, they also trigger conformational change in the dimeric capsomere creating the A/B quasi-conformer, 60 of which are needed to complete the T =3 capsid. This is the most compelling demonstration to date that this ssRNA virus, and by implications potentially very many of them, assemble via a PS-mediated assembly mechanism.